Conflict-sensitive Climate Action: Addressing the root drivers conflict and fragility. CGIAR Issue Brief Series for Informing COP29 | Number 8 - Medina, Leonardo; Pacillo, Grazia; Madurga-Lopez, Ignacio; Läderach, Peter (CGIAR, 2024)
Understanding the complex interactions among climate effects, climate action, and the socio-political and economic factors driving conflict is critical to advise global climate strategies. While climate change can exacerbate tensions, it is political interests and resources to arm, organize, and sustain conflict that escalate grievances related to climate change impacts (e.g., drought, water scarcity, or food insecurity) into violence. Addressing climate change alone will not fully prevent conflicts from emerging. Instead, attention must be given to reducing the financial flows and political incentives that fuel organized violence while enhancing conflict-sensitive climate strategies. Accountable institutions and inclusive governance are essential for managing climate-conflict linkages.